Acrylonitrile-butadiene-styrene toughened nylon 6: The influences of compatibilizer on morphology and impact properties - Araújo, E. M.; Hage, E.; Carvalho, A. J. F. (Wiley, 2002)
Polymer alloys have been used as an alternative to obtain polymeric materials with unique physical properties. Generally, the polymer mixture is incompatible, which makes it necessary to use a compatibilizer to improve the interracial adhesion. Nylon 6 (PA6) is an attractive polymer to use in engineering applications, but it has processing instability and relatively low notched impact strength. In this study, the acrylonitrile-butadiene-styrene (ABS) triblock copolymer was used as an impact modifier for PA6. Poly(methyl methacrylate-co-maleic anyhydride) (MMA-MA) and poly(methyl methacrylate-co-maleic methacrylate) (MMA-GMA) were used as compatibilizers for this blend. The morphology and impact strength of the blends were evaluated as a function of blend composition and the presence of compatibilizers. The blends compatibilized with maleated copolymer exhibited an impact strength up to 800 J/m and a morphology with ABS domains more efi8ciently dispersed. Moderate amounts of MA functionality in the compatibilizer (∼5%) and small amounts of compatibilizer in the blend (∼5%) appear sufficient to improve the impact properties and ABS dispersion. © 2002 Wiley Periodicals, Inc. J Appl Polym Sci 87.
Keywords: Blends; Compatibilization; Nylon; Toughness; Butadiene; Copolymers; Polymer blends; Strength of materials; Styrene; Toughened nylons; Nylon polymers; nylon 6